In loco parentis: The adoption plot in Dutch-language colonial children’s books - Wesseling, Elisabeth (Tydskrif vir Letterkunde, 2009)
This article analyzes the “adoption plot” in colonial children’s literature from the 1950s, which narrates how black children are socialized into Western civilization. Many children’s books about the colonies have been inspired by missionary stories dating from the 1900s about the conversion of black children. Children’s literature generalizes these stories into abstract symbolic structures that can be easily reiterated in other contexts. The enduring relevance of the adoption plot is not to be underestimated. We still tend to conceive of Third World children as essentially parentless and as such, up for adoption by First World citizens, as the imagery of international relief demonstrates.